Structural asymmetry and discrete nucleic acid subdomains in the Trypanosoma brucei kinetoplast. - Gluenz, E; Shaw, M; Gull, K (2007)
The mitochondrial genome of Trypanosoma brucei is contained in a specialized structure termed the kinetoplast. Kinetoplast DNA (kDNA) is organized into a concatenated network of mini and maxicircles, positioned at the base of the flagellum, to which it is physically attached. Here we have used electron microscope cytochemistry to determine structural and functional domains involved in replication and segregation of the kinetoplast. We identified two distinct subdomains within the kinetoflagellar zone (KFZ) and show that the unilateral filaments are composed of distinct inner and outer filaments. Ethanolic phosphotungstic acid (E-PTA) and EDTA regressive staining indicate that basic proteins and DNA are major constituents of the inner unilateral filaments adjoining the kDNA disc. This evidence for an intimate connection of the unilateral filaments in the KFZ with DNA provides support for models of minicircle replication involving vectorial export of free minicircles into the KFZ. Unexpectedly however, detection of DNA in the KFZ throughout the cell cycle suggests that other processes involving kDNA occur in this domain. We also describe a hitherto unrecognized, intramitochondrial, filamentous structure rich in basic proteins that links the kDNA discs during their segregation and is maintained between them for an extended period of the cell cycle.